Rekonstruksi Pembelajaran Kitabah Berbasis Digital di Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darul A’mal Lampung - Joni Kawijaya; Riski Rusmalinda (ANWARUL, 2025)
Writing in Arabic (kitabah) remains a significant challenge, with only 31.1% of students able to produce formal texts with correct structure, while 68.9% struggle with diction selection and sentence construction. A preliminary study involving 22 fourth-semester students in the Arabic Language Education Program revealed a gap between instructional goals and classroom reality, largely due to monotonous conventional methods and one-way interactions lacking adequate feedback (70%). This study aims to examine the effectiveness of integrating e-learning and digital dictionaries using a mixed-method approach. Quantitative analysis was conducted through pre-test and post-test in the experimental group, while qualitative data were gathered via interviews and observations. Statistical results showed a significant improvement in the average score from 58.67 to 82.27 (Sig. 0.000), with a gain score of 0.63. Qualitatively, digital dictionary features enhanced learner autonomy and writing speed, while digital rubrics enabled instructors to provide more objective feedback. Nonetheless, the implementation faced challenges such as limited digital literacy and infrastructure readiness. The study concludes that technology integration is effective in improving students’ kitabah competence. The implications highlight the need for digital literacy training, the development of more inclusive platforms, and the refinement of AI-based assessment systems. Further research is recommended to evaluate the model's effectiveness across larger and more diverse institutional samples.